Environmental performance measurement in arts and cultural organisations: Exploring factors influencing organisational changes. (15th January 2023) - Domingues, Ana Rita; Mazhar, Muhammad Usman; Bull, Richard
Abstract: Arts and Cultural Organisations (ACOs) have received significant attention over the last few years regarding their environmental performance. ACOs are often non-profit organisations, relying on government funding to implement various programmes to support societal development. Funding dependence can shift ACOs' focus from creating socio-cultural value to being more commercially driven. This paper explores factors influencing organisational changes in ACOs related to environmental performance measurement. Stakeholders in ACOs based in Nottingham, England, were interviewed and participated in a workshop to validate and collect additional data. Our research uncovered five interrelated factors that influence organisational change: the role of funding bodies; local policies and networks; organisational culture and leadership; lack of resources; and building proprietary-tenant relationships. This paper contributes to understanding ACOs responses to measuring environmental performance and the challenges they face as they move from measuring to implementation. Implications are explored for how funding is allocated and understood in terms of moving beyond merely measuring the carbon footprint of activities. ACOs' funding dependence indicates a focus on carbon measurement, omitting a more holistic approach towards the environment and sustainability. Highlights: Arts and cultural organisations based in Nottingham participated in the research. Current ACE funding leads to the implementation of a dominant environmental agenda. Environmental performance measurement is incomplete and focused on carbon emissions. ACOs lack the wider support to adopt a whole systems approach to sustainability. Further research should focus on the importance of place and context in ACOs behaviour.